Community analysis as socio-economic system: space-territorial nature, functions and features - Savchuk, Dmytro (Technology audit and production reserves, 2017)
The object of research is society as a socio-economic system, its spatial-territorial nature, functions and characteristics. One of the most problematic places is that often there is inconsistency and lagging of the line ministries from the existing rates of decentralization and their response to specific uncertainties. In addition, the problem is personnel shortage in the newly unified territorial communities, there are not enough skilled workers to successfully advance the communities in development. In the course of the study, methods were used: logical generalization, analogies, comparative comparison, analysis and synthesis. In particular, these methods have made it possible to identify through which some deficiencies can be eliminated through the legislative regulation of the formation of new communities. A comprehensive analysis of the spatial-territorial nature and functions of the joint territorial communities is obtained. Recommendations are proposed for improving the legislative regulation of the association of territorial communities. In particular, let’s believe that it would be appropriate and justified to border communities of different regions with similar socio-economic factors to unite in one community. Let’s suggest that in the new Law "On the administrative and territorial structure of Ukraine" there be an article on the possibility of joining territorial units to existing communities, which inhabitants historically, territorially and culturally benefit from the benefits of the corresponding center of the community, but de jure is part of another area. In comparison with similar well-known studies in the field of administrative-territorial reform and local self-government, this study provides an opportunity to comprehensively analyze society as a socio-economic system. In particular, due to the improvement of legislative regulation, it is possible to achieve a positive social and economic effect in the process of creating new unified territorial communities